Studies about paramilitarism in colombia (2007)
This article presents focuses, conceptions, hypotheses and methodologies that build up the bibliography of paramilitarism in Colombia, also briefing a series of new study perspectives of the phenomenon such as discourse analysis, complexity centered focus, organizational analysis, and theoretical perspectives. Finally, some gaps in the literature are highlighted.